Concepções de gramática e de ciência no ensino de língua - Kaodoinski, Fabiana (My University, 2015)
This thesis has as main objective to investigate normative, descriptive and internalized grammar conceptions, describing them, seeking approaches with science conceptions and verifying if they present contributions to the native tongue teaching in Basic Education. The research was essentially bibliographical, basing itself on theoretical references of Saussure, Benveniste, Bakhtin, Vygotsky, Bronckart, Kuhn, Morin, Paviani, Franchi, Travaglia, Possenti, Flores, Pozo, Cavaliere, among other authors that investigate education, language, epistemology, teaching and learning processes and the questions related to mother tongue and grammar. It was observed that the descriptive grammar aims, as its own title says, to describe the language to perceive possible or not-possible uses, and it may aid the student to understand the linguistic working. The internalized grammar, in turn, can bring benefits to the native tongue teaching for the fact that of recognizing and not devaluating the language rules learned by the students in their speaking community. Thus, this conception suggests that the teacher identifies the linguistic reality of the students so he/she can elaborate activities such as to allow them to access new forms of expression. As for the normative grammar, it was understood that it’s teaching must be rethought. Furthermore, the study allowed to find that, on portuguese language class, the work based on rules transmission and on phrases or isolated words, which was related to the conception of normative grammar and with the cartesian-newtonian science conception, may be reviewed. As an alternative, the realization of activities that contemplate de text/speech was recommended. This meets the contemporary science conception, grounded on characteristics such as unity, complexity, systemic view. The investigation also allowed to conclude that the prescriptive character of normative grammar can attach itself to the idea advocated by the cartesian-newtonian paradigm that there are absolute truths. In this perspective, it is alternatives connected to the conception of education and language as interaction, coined on intersubjectivity, were suggested.
Esta dissertação tem como objetivo principal investigar concepções de gramática normativa, descritiva e internalizada, descrevendo-as, buscando aproximações com concepções de ciência e verificando se apresentam contribuições ao ensino de língua materna na Educação Básica. A pesquisa foi essencialmente bibliográfica, fundamentandose em referenciais teóricos de Saussure, Benveniste, Bakhtin, Vygotsky, Bronckart, Kuhn, Kant, Morin, Paviani, Franchi, Travaglia, Possenti, Flores, Pozo, Cavaliere, entre outros autores que investigam a educação, a linguagem, a epistemologia, os processos de ensino e de aprendizagem e as questões relacionadas à língua materna e à gramática. Observou-se que a gramática descritiva busca, como o próprio nome diz, descrever a língua para perceber usos possíveis, podendo auxiliar o aluno a compreender o funcionamento linguístico. A gramática internalizada, por sua vez, pode trazer benefícios ao ensino de língua portuguesa pelo fato de reconhecer e não desvalorizar as regras da língua aprendidas pelos estudantes em sua comunidade de fala. Assim, essa concepção sugere que o professor identifique a realidade linguística dos alunos para poder elaborar atividades as quais possibilitem a eles o acesso a novas formas de expressão. Quanto à gramática normativa, entendeu-se que seu ensino precisa ser repensado. Além disso, a pesquisa permitiu constatar que, na aula de língua portuguesa, o trabalho com base em frases ou palavras isoladas e na transmissão de regras, o qual foi relacionado com a concepção de gramática normativa e com a de ciência cartesiana-newtoniana, pode ser revisto. Como alternativa, indica-se a realização de atividades que contemplem o texto/discurso. Isso vai ao encontro da concepção contemporânea de ciência, alicerçada em características como a unidade, a complexidade, a visão sistêmica. A investigação também permitiu concluir que o caráter prescritivo da gramática normativa pode ligar-se à ideia defendida pelo paradigma cartesiano-newtoniano de que existem verdades absolutas. Nessa perspectiva, sugerem-se alternativas ligadas à concepção de educação e de linguagem como interação, cunhadas na intersubjetividade.
Keywords: Língua portuguesa - Gramática; Análise do discurso; Linguística; Educação; Portuguese language - Grammar; Discourse analysis; Linguistics; Education